Investigating the efficiency of the Beijing Faint Object Spectrograph and Camera (BFOSC) of the Xinglong 2.16-m reflector. (August 2018) - Zhao, Yong; Fan, Zhou; Ren, Juan-Juan; Ge, Liang; Zhang, Xiao-Ming; Li, Hong-Bin; Wang, Hui-Juan; Wang, Jian-Feng; Qiu, Peng; Jiang, Xiao-Jun
Abstract: The Beijing Faint Object Spectrograph and Camera (BFOSC) is one of the most important instruments operating in conjunction with the 2.16-m telescope at Xinglong Observatory. Every year there are ∼20 SCI-papers published based on observational data acquired with this telescope. In this work, we have systemically measured the total efficiency of the BFOSC that operates as part of the 2.16-m reflector, based on observations of two ESO flux standard stars. We have obtained the total efficiencies of the BFOSC instrument of different grisms with various slit widths in almost all ranges, and analyzed factors which effect the efficiency of this telescope and spectrograph. For astronomical observers, the result will be useful for them to select a suitable slit width, depending on their scientific goals and weather conditions during observations. For technicians, the result will help them to systemically identify the real efficiency of the telescope and spectrograph, and to further improve the total efficiency and observing capacity of the telescope technically.